Analyzing The Effect of Cylinder Liner Bronze Alloys on Hardness - Hasbullah, Ichsan; Pratama, Aditya Wahyu (Department of Mechanical Engineering, Universitas Andalas, 2024)
The quality of a component material is a significant issue in today's society, where the concept of